2013
DOI: 10.1515/joepi-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SCN1A mutations in patients with severe myoclonic epilepsy in infancy by custom resequence array

Abstract: introduction. Very few epilepsy phenotypes have been associated with causative genes; nevertheless, it is becoming possible, for some epilepsy phenotypes, to predict the most efficacious anti-epileptic drugs for patients based on their genetic makeup. The development of individualized medicine based on genetic information and the genetic diagnosis of epilepsy are expected to greatly improve the diagnosis and treatment of epilepsy. Here, we developed a DNA array (resequencing array) for the genetic diagnosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A Japanese Group (Hirosaki University) developed and tested a new version of the EpiGene that contains 35 genes and includes genes responsible for the side effects of AEDs (Sugawara et al, 2013). These authors showed that for some epilepsy phenotypes it is becoming possible to predict the most efficacious antiepileptic drugs for patients based on their genetic makeup (Yamada et al, 2013;Sugawara et al, 2013).…”
Section: Genetic Testing In the Epilepsiesmentioning
confidence: 99%
“…A Japanese Group (Hirosaki University) developed and tested a new version of the EpiGene that contains 35 genes and includes genes responsible for the side effects of AEDs (Sugawara et al, 2013). These authors showed that for some epilepsy phenotypes it is becoming possible to predict the most efficacious antiepileptic drugs for patients based on their genetic makeup (Yamada et al, 2013;Sugawara et al, 2013).…”
Section: Genetic Testing In the Epilepsiesmentioning
confidence: 99%